MED28 increases the colony-forming ability of breast cancer cells by stabilizing the ZNF224 protein upon DNA damage - Cho, Jin Gu; Lim, Key Hwan; Park, Sang Gyu (Oncology Letters, 2018)
The regulation of gene expression by transcription factors serves a critical function in cell proliferation. Zinc-finger protein 224 (ZNF224), a Krüppel-associated-box-containing zinc finger protein, is known to serve a crucial function in integrating the transcriptional co-factors that activate transcriptional regulation pathways in the cell. A previous study demonstrated that ZNF224 enhances cell proliferation by downregulating the expression of p21 and p53. The present study identified mediator complex subunit 28 (MED28) as a potential binding partner for ZNF224; this was confirmed by co-immunoprecipitation and a surface plasmon resonance assay. Additionally, the KRAB domain at the N-terminal of ZNF224 interacts with the MED domain of MED28. Bimolecular fluorescence complementation analysis revealed that ZNF224 associates with MED28 in the nucleus. In addition, ZNF224 was rapidly degraded upon treatment with the DNA-damaging agent camptothecin (CPT). Transient overexpression of MED28 inhibited the CPT-mediated degradation of ZNF224, resulting in increased colony formation by MCF-7 cells. The molecular mechanisms that underlie the biological outcomes of MED28 expression have not yet been fully elucidated. The present study provides molecular evidence for the function of ZNF224 and MED28 in the DNA-damage response.
Keywords: Breast cancer; Cancer cell proliferation; DNA damage; Mediator complex subunit 28; Zinc-finger protein 224